Pengaruh Sistem Informasi Pemerintahan Daerah, Sistem Pengendalian Internal, Good Governance, dan Kualitas Sumber Daya Manusia terhadap Kualitas Laporan Keuangan Pemerintah Daerah Pemerintah Kota Probolinggo - Sinta Angraini; Zuraidah Zuraidah (Universitas Pendidikan Ganesha, 2026)
This study aims to analyze the influence of the Regional Government Information System, Internal Control System, Good Governance, and human resource quality on the quality of local government financial statements in the Probolinggo City Government. The quality of financial statements is an important indicator in creating transparent and accountable governance. Although the Probolinggo City Government has obtained an Unqualified Opinion, several obstacles are still found in the preparation of financial statements, such as reporting delays, system network disruptions, and limited employee capability in operating digital financial applications. This study used a quantitative approach with an explanatory research type. Data were collected through questionnaires distributed to 122 regional apparatus employees involved in regional financial management. Data analysis was conducted using variance-based structural equation modeling with the assistance of SmartPLS 3 software. The results showed that the Regional Government Information System had a negative and significant effect on the quality of local government financial statements. Meanwhile, the Internal Control System, Good Governance, and human resource quality had a positive and significant effect on the quality of local government financial statements. Good Governance and human resource quality were the most dominant factors in improving the quality of financial statements. This study concludes that the quality of local government financial statements is influenced by governance practices, the effectiveness of internal control, employee competence, and the optimal implementation of information systems.